2019
DOI: 10.3390/en12152942
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Electromobility in Poland and EU States as a Tool for Management of CO2 Emissions

Abstract: The article analyzes the dynamics of the development of the electromobility sector in Poland in the context of the European Union and due to the economic situation and development of the electromobility sector in the contexts of Switzerland and Norway. On the basis of obtained data, a forecast was made which foresees the most likely outlook of the electric car market in the coming years. The forecast was made using the creeping trend method, and extended up to 2030. As part of the analysis of the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 71 publications
0
53
0
4
Order By: Relevance
“…In the U.S., Barari and Kundu [87] revisited the role of the U.S. Federal Reserve in triggering the recent housing crisis by using a VAR model and found that federal funds rate did not lead to house price increases. Looking at the European Union, Tucki et al [88] proposed a new method to investigate the development of the electromobility sector in Poland and the EU states. Their study concluded that Poland and the EU states require new approaches in terms of energy management and vehicle operation management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the U.S., Barari and Kundu [87] revisited the role of the U.S. Federal Reserve in triggering the recent housing crisis by using a VAR model and found that federal funds rate did not lead to house price increases. Looking at the European Union, Tucki et al [88] proposed a new method to investigate the development of the electromobility sector in Poland and the EU states. Their study concluded that Poland and the EU states require new approaches in terms of energy management and vehicle operation management.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It also supported the goal of reducing 37% of GHG emissions by 2025, compared to 2005 levels [2,12,15,16]. Differently, some European Union countries also include electromobility (electric cars) in their GHG emission reduction forecasts [17].…”
Section: Introductionmentioning
confidence: 96%
“…The dynamic development of global economy and the globalization of automotive sectors require a multi-dimensional view [1,2]. Increased public awareness of the issues of reducing CO 2 emissions has accelerated work on the development of electromobility [3,4] and biofuels [5,6]. One of the most important parts of car engineering is the tire [7,8].…”
Section: Introductionmentioning
confidence: 99%